A Review of Understand Film Studies - Ali Sheikhmehdi; Arsalan Moghadas (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2020)
The book Understand Film Studies aims to equip its reader with necessary concepts for film critique; in this regard, the author describes the definitions of aesthetic and film structure, film genres and documentary, and by giving examples and expressing the basic concepts of each one, it aims to clarify the topics. The author presents 10 different approaches for cinematic studies, and then pays attention to different techniques to create the images. The author also indicates the distinction between realist and formalist theoreticians and argues that both approaches are useful.  However, the 10 approaches mentioned in the book do not have enough precision and comprehensiveness for film analysis. The emphasis on Hollywood films and special privileges for the director as auteur, despite the subsequent text-based analysis, reduces the updated content of the book.